Conceptualizing interactive installations to enrich the experience of public library users - Cuello, Amanda (My University, 2013)
The role of public libraries in society is evolving due to the continuous development of new technologies that support the dissemination of knowledge; however, this does not mean that libraries are disappearing. In order to keep providing access to knowledge, among other things, libraries must embrace and integrate both physical and digital space in their identity and in the way users perceive them. The purpose of this Master Thesis has been to explore the opportunities for integration of physical and digital spaces through the design of interactive installations for public libraries. Specifically, the project consisted in the design of a concept for an interactive installation for Hisingen’s Library in Gothenburg using co-design workshops and other activities for user involvement. In addition to the aforementioned design, a series of recommendations for concept design and methods for the design of interactive interventions in libraries has been compiled in order to inform further work in the topic. The concept that was developed served as an example of future possibilities for public libraries in which user participation and integration of physical and digital services improve the way people search and experience content.
Keywords: Informations- och kommunikationsteknik; Människa-datorinteraktion (interaktionsdesign); Information & Communication Technology; Human Computer Interaction